2015
DOI: 10.1111/socf.12167
|View full text |Cite
|
Sign up to set email alerts
|

Compensation and Community Corrosion: Perceived Inequalities, Social Comparisons, and Competition Following the Deepwater Horizon Oil Spill

Abstract: After disasters, victim compensation programs are typically associated with individual healing and community rebuilding. But post-disaster compensation systems also have the potential to introduce confusion and competition, further fraying the social fabric of communities affected by trauma. To assess the perceived effects of disaster compensation processes on community social relations, as well as the mechanisms that underlie such effects, we turn to the case of the Deepwater Horizon oil spill, after which BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 42 publications
(71 reference statements)
0
21
0
Order By: Relevance
“…10 Indeed, research on the post-DHOS compensation process suggests that perceptions of randomness and lack of transparency in the distribution of claims resulted in negative social comparisons and competition that led to a corrosive effect in the community. 44 Such characteristics of corrosive communities may explain why we observe a negative impact of the oil spill on cognitive social capital and social support.…”
Section: Discussionmentioning
confidence: 90%
“…10 Indeed, research on the post-DHOS compensation process suggests that perceptions of randomness and lack of transparency in the distribution of claims resulted in negative social comparisons and competition that led to a corrosive effect in the community. 44 Such characteristics of corrosive communities may explain why we observe a negative impact of the oil spill on cognitive social capital and social support.…”
Section: Discussionmentioning
confidence: 90%
“…The spill uncovered a credibility gap in the ability of the current U.S. policy network (e.g., Clean Water Act, Oil Pollution Act) to prevent ecological disasters, and protect human and ecological health, and help populations get compensation for their losses [54]. Minority communities - such as Vietnamese American communities - along the Gulf may have been disproportionately impacted by the spill [56]. Other research has demonstrated the toll levied on communities navigating the claims process [56], and due to language and cultural barriers, these insular communities may have faced greater barriers in seeking remediation [55].…”
Section: Discussionmentioning
confidence: 99%
“…Minority communities - such as Vietnamese American communities - along the Gulf may have been disproportionately impacted by the spill [56]. Other research has demonstrated the toll levied on communities navigating the claims process [56], and due to language and cultural barriers, these insular communities may have faced greater barriers in seeking remediation [55]. Health policies are created to inherently provide protection and either incentives or fines to promote adherence.…”
Section: Discussionmentioning
confidence: 99%
“…"Interim payments for many claimants came quickly, designed to replace one month of lost income due to fisheries and tourism closure. From April 25th through August 23rd, BP received 154,000 claims and wrote 127,000 checks covering $399 million in estimated damages" (Mayer et al 2015). Despite this seemingly impressive rate of paying out, "BP's claims data from that summer suggest that only one third of the total claims submitted were actually fulfilled" (Mayer et al 2015).…”
Section: Tf 1: a Willingness To Cooperatementioning
confidence: 99%